HERRAMIENTAS DE TECNOLOGÍA DE GESTIÓN EN LIMA METROPOLITANA - Huaco Pastor, Enrique (2009)
The economic, social, political, technological operated these past three decades have allowed technology to become an essential element in the strategies of organizations, for their survival, growth and achievement of the objectives outlined for them, sustainable time, with productivity, quality, competitiveness and profitability within a local and global environment. The Peru, as a society made up of business organizations, among others, the presence of technologies for the civilization of agriculture, industrial civilization and the civilization of knowledge, many of these business units with levels of technology application rudimentary or emerging management and other business units with higher levels of modernity. The purpose of the research study will be aimed at the identification of key management tools that exist plexus administrative disciplinary science in the field of business organizations in metropolitan Lima, and which of them are applicable in the business units , investigating and developing the description of their paradigms and to make proposals to strengthen the incorporation into the application of technological tools embedded in paradigms that stimulate and modernize the business units tended to be accepted in its operating standards to compete on a global dimension.